2020
DOI: 10.1007/s40592-020-00121-1
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions on Controlled Human Infection Model (CHIM) studies—a qualitative pilot study from South India

Abstract: Research using Controlled Human Infection Models is yet to be attempted in India. This study was conducted to understand the perceptions of the lay public and key opinion makers prior to the possible introduction of such studies in the country. 110 respondents from urban and rural Bangalore district were interviewed using qualitative research methods of Focus Group Discussions and In-depth Interviews. The data was analyzed using grounded theory. Safety was a key concern of the lay public, expressed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…The issue of riskallowances and health insurance pointed to participants' concern about how researchers would take care of unforeseen or unanticipated research-related illnesses. Similar problems were noted in a study done in India that reported on public perceptions of HIS 27 . The study paid for no-fault insurance for participants to compensate for those who would sustain researchrelated injuries.…”
Section: Discussionsupporting
confidence: 81%
“…The issue of riskallowances and health insurance pointed to participants' concern about how researchers would take care of unforeseen or unanticipated research-related illnesses. Similar problems were noted in a study done in India that reported on public perceptions of HIS 27 . The study paid for no-fault insurance for participants to compensate for those who would sustain researchrelated injuries.…”
Section: Discussionsupporting
confidence: 81%
“…The issue of risk-allowances and health insurance pointed to participants' concern about how researchers would take care of unforeseen or unanticipated research-related illnesses. Similar problems were noted in a study done in India that reported on public perceptions of CHIM 29 . The MARVELS feasibility study paid for no-fault insurance for participants to compensate for those who would sustain research-related injuries.…”
Section: Discussionsupporting
confidence: 81%
“…This process of engagement was recommended by Ugandan stakeholders in preparation for CHI-S (Elliott et al, 2018 ). Similarly, other CHI studies have also recommended and conducted community engagements with the target communities in disease-endemic countries such as Zambia (Kunda-Ng’andu et al, 2021 ), Vietnam (Kestelyn et al, 2019 ), India (Vaz et al, 2019 , 2020 ), Malawi (Kapumba et al, 2020 ), Kenya (Njue et al, 2018 ), and Gabon (Alabi et al, 2021 ). The studies showed that participants are able to understand the processes involved during a CHI.…”
Section: Discussionmentioning
confidence: 99%
“…Participant selection for CHI gives prominence to the ethical need for equity in the process (Bambery et al, 2016 ) and exploitation of vulnerable groups (Rose, 2018 ). Purposeful participant inclusion and exclusion enables that those selected are able to understand the nature of the CHI-S (Rose, 2018 ) and covers a representative group of people (Vaz et al, 2020 ). The former allows particpants to raise their views and concerns as seen elsewhere (Hodgson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%